Preparation method of micro-nano particle TEM (Transmission Electron Microscope) sample

Through the method of resin embedding and curing of micro-nanoparticles, the problems of resin thermal deformation and sample bending in the existing TEM sample preparation methods are solved, and efficient and straight film sample preparation is achieved, which improves the preparation efficiency and success rate.

CN119469976APending Publication Date: 2025-02-18QINGDAO UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411747214.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing TEM sample preparation methods are complex in operation and low in success rate. The resin is prone to thermal deformation and cracking under the action of electron beam and ion beam, causing the sample to bend or rupture, affecting the sample quality and preparation efficiency.

Method used

The resin embedded curing micro-nanoparticles was used to uniformly mix the resin with the micro-nanoparticles and cure them on a copper net. The straight film sample was obtained by cutting, thinning and refining through FIB-SEM dual-beam electron microscope.

Benefits of technology

It effectively relieves stress during sample preparation, avoids the resin thermal deformation and cracking, shortens sample preparation time, improves preparation efficiency and success rate, and reduces technical dependence on operators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119469976A_ABST
    Figure CN119469976A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of transmission electron microscope samples, and particularly discloses a preparation method of a micro-nano particle TEM (Transmission Electron Microscope) sample, which comprises the following steps: preparing resin, embedding and curing the resin on a copper mesh, and cutting, thinning and finishing by using an FIB-SEM (FIB-Scanning Electron Microscope) double-beam electron microscope to form a thin film sample, so that a plurality of precision steps in the traditional FIB-SEM double-beam electron microscope for preparing the thin film sample are reduced, and the production efficiency is improved. The preparation time of the sample can be shortened from 2 hours to about 10 minutes, the degree of dependence on the operation technology of preparation personnel is also greatly reduced, and the thermal deformation and cracking phenomena of the resin are avoided under the action of electron beams and ion beams, so that the stress of the film sample in the preparation process is relieved, and the film sample is more stable in performance. The method has the advantages that the method is simple and convenient to operate, the obtained film sample cannot be bent or broken, the obtained film sample is straight and ideal, and micro-nano particles in a plurality of meshes in the same copper net can be processed, so that a plurality of TEM samples can be manufactured at one time, and the sample preparation efficiency and success rate are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of transmission electron microscope sample preparation, and in particular to a micro-nano particle TEM sample preparation method based on resin embedding and curing. Background Art

[0002] In the characterization and analysis methods of chemical materials or biological materials, the transmission electron microscope (TEM) is often used. It is a kind of microscope that transmits the accelerated and focused electron beam to a very thin sample, so that the electrons collide with the atoms in the sample and change their direction, thereby producing three-dimensional angle scattering. The size of the scattering angle is closely related to the density and thickness of the sample, so it can form images of different brightness and darkness. The image is then magnified and focused and displayed on an imaging device (such as a fluorescent screen, film, and photosensitive coupling component). Therefore, it is a microscope that can specifically analyze the morphology, composition, structure and other information of thin film samples. However, due to the limited penetration ability of the transmission electron microscope, it is necessary to prepare the bulk or micro-nano particle samples into thin slices when performing analysis.

[0003] Traditional sample preparation methods are complex, have low success rates, and take a long time. It usually takes about a day to prepare a suitable sample. In recent years, the use of focused ion beam (FIB) to prepare TEM samples has increased. For example, the use of FIB-SEM dual-beam electron microscopes to prepare transmission electron microscope samples has gradually increased. The entire process is to use the ion beam processing capability to protect the selected parts of the sample, cut and extract, and perform thinning to finally obtain a sample suitable for TEM observation. Specifically, it includes steps such as Platinum deposition, Bulk-out, U-cut, Lift-out, Mount on Cu half-grid, and Final milling. Even though the above method has greatly improved the efficiency of sample preparation, the above steps are delicate and require high technical skills of the operator. Therefore, making an ideal TEM sample often still requires a skilled operator to complete it in 1 to 2 hours, or even longer. In addition, during the TEM sample preparation process, as the sample thickness continues to decrease, the concentration of residual stress in the sample will cause the thin film sample to bend or curl, which to a certain extent affects the quality of the TEM sample and its analytical use effect. Based on this, it is necessary to further improve the TEM sample preparation method to solve the above problems. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing micro-nano particle TEM samples in which the resin will not experience thermal deformation or cracking under the action of electron beams and ion beams, the stress in the sample preparation process is relieved, and no bending or cracking occurs, so that the obtained thin film sample is straight and ideal, the sample preparation time can be greatly shortened, the dependence on the operating technology of the preparation personnel is reduced, and the preparation efficiency and success rate are effectively improved.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: a method for preparing micro-nano particle TEM samples, comprising the following steps: Step 1, preparing a resin for embedding and curing micro-nano particles; Step 2: preparing the resin and acetone to obtain a resin mixture, taking at least two portions of the resin mixture, adding different amounts of the micro-nano particles to each portion of the resin mixture, and mixing them evenly and fully to obtain a sample mixture, embedding and curing the sample mixtures of various concentrations on correspondingly set copper meshes and placing them in an oven for polymerization, wherein the mesh aperture of the copper mesh is larger than the particle size of the micro-nano particles; Step 3, placing the polymerized copper mesh into a FIB-SEM double-beam electron microscope, placing one at a time and applying an electron voltage of 30 kV, and screening out the copper mesh with an average distance between the micro-nano particles between 20 and 500 um by observing the distribution of the micro-nano particles on the copper mesh; Step 4, fixing the screened copper mesh onto a sample stage tilted in the FIB-SEM dual-beam electron microscope; Step 5: After the sample stage of the FIB-SEM dual-beam electron microscope is tilted and adjusted, the micro-nano particles dispersed, centered in the mesh of the copper mesh, and connected with resin around are selected as particle samples, a Pt protective coating is evaporated on the surface to be processed of the particle sample, and the voltage and current are adjusted after cutting it to the target thickness, and the angle of the sample stage is fine-tuned within the range of ±3° to thin and refine the particle sample to obtain a thin film sample. During the cutting, thinning and refining process, both ends of the particle sample are ensured to be connected to the resin so that the obtained thin film sample can remain flat; Step six: transfer the copper mesh with the thin film sample to TEM for observation and analysis.

[0006] As a preferred technical solution, the resin includes components in the following proportions: 7 g of ERL4221 epoxy resin, 5 g of DER736 plasticizer, 15 g of NSA curing agent, and 200 ul of DMAE catalyst.

[0007] As a preferred technical solution, the resin preparation method is: use a plastic pipette to suck and weigh 7g of ERL4221 epoxy resin and 5g of DER736 plasticizer respectively, place the weighed ERL4221 epoxy resin and DER736 plasticizer in a plastic centrifuge tube in turn and mix them evenly, and then add 15g of NSA curing agent and 200ul of DMAE catalyst in turn after at least 10 minutes. Each component must be fully mixed after adding, and the time interval between adding NSA curing agent and DMAE catalyst is at least 10 minutes.

[0008] As a preferred technical solution, when preparing the sample mixed solution in step 2: 20ul of the resin and 180ul of the acetone are added to a 1.5ml conical bottom centrifuge tube in sequence to obtain the resin mixed solution; The micro-nano particles are taken with a toothpick and added into the resin mixed solution to form the sample mixed solution.

[0009] As a preferred technical solution, the resin mixture is prepared in 10 tubes in equal amounts, and the micro-nano particles are taken 10 times with a toothpick, so that the amount of the micro-nano particles taken each time increases gradually, and mixed to form 10 tubes of the sample mixture; The sample mixture was shaken tube by tube using a vortex shaker for 1 minute to achieve full dispersion of the micro-nano particles in the resin and the acetone.

[0010] As a preferred technical solution, a tube of the sample mixture is obtained each time the oscillation is completed, and then 1 ul is drawn from the tube and dropped onto the carbon support film of the copper mesh, and the copper mesh is placed on tin foil; After obtaining 10 copper meshes with the sample mixture, put them together in an oven at 60° for polymerization for at least 48 hours.

[0011] As a preferred technical solution, in step five, the sample stage of the FIB-SEM dual-beam electron microscope needs to be tilted and adjusted by 10°.

[0012] Due to the adoption of the above technical scheme, the present invention has the following beneficial effects: the micro-nano particles are embedded and solidified into the copper mesh by using resin, and a thin film sample is obtained after cutting, thinning and finishing by FIB-SEM dual-beam electron microscope, and the copper mesh with the thin film sample is transferred to TEM for observation and analysis, thereby reducing the steps of U-cut, Lift-out, Mount on Cu, half-grid and the like in the preparation of thin film samples by traditional FIB-SEM dual-beam electron microscope, and the sample preparation time can be shortened from the faster 2 hours to about 10 minutes, and the sample preparation time is greatly shortened. Since the above-mentioned multiple precise steps are not involved, the dependence on the operating technology of the preparation personnel is also greatly reduced, and the resin will not be thermally deformed or cracked under the action of electron beam and ion beam, so that the stress of the thin film sample in the preparation process is relieved, and the obtained thin film sample will not bend or crack, so that the obtained thin film sample is straight and ideal, and the efficiency and success rate of sample preparation are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The following drawings are intended only to illustrate and explain the present invention, and are not intended to limit the scope of the present invention. Figure 1 Schematic diagram of micro-nano particles being embedded and cured on a copper mesh using resin in an embodiment of the present invention; Figure 2 is a simplified process flow chart of preparing TEM samples according to an embodiment of the present invention; Figure 3 It is a partial schematic diagram of micro-nano particles embedded and solidified in a mesh of a copper mesh according to an embodiment of the present invention; Figure 4 Schematic diagram of an NCM film sample obtained by processing a resin-embedded NCM (nickel-cobalt-manganese ternary material) particle sample using a FIB-SEM dual-beam electron microscope in an embodiment of the present invention; Figure 5 This is an image of the NCM particle sample prepared in an embodiment of the present invention in a TEM; Figure 6 This is the diffraction image of the atomic arrangement and single crystal structure of the NCM film sample of the embodiment of the present invention observed in the TEM. DETAILED DESCRIPTION

[0014] The present invention is further described below in conjunction with the accompanying drawings and examples. In the following detailed description, certain exemplary embodiments of the present invention are described only by way of illustration. Needless to say, those of ordinary skill in the art will recognize that the described embodiments may be modified in various ways without departing from the spirit and scope of the present invention. Therefore, the drawings and description are illustrative in nature and are not intended to limit the scope of protection of the claims.

[0015] like Figures 1 to 4As shown, a method for preparing a micro-nanoparticle TEM sample comprises the following steps: Step 1: Prepare the resin for embedding and curing the micro-nanoparticles to help the thin film sample maintain an ideal straight state when forming it, so as to prevent it from bending or breaking, thereby ensuring the smoothness and accuracy of observation and analysis using TEM.

[0016] The resin includes the following components: 7g of ERL4221 epoxy resin, 5g of DER736 plasticizer, 15g of NSA curing agent, and 200ul of DMAE catalyst. The resin is prepared by using a plastic pipette to suck and weigh 7g of ERL4221 epoxy resin and 5g of DER736 plasticizer respectively, placing the weighed ERL4221 epoxy resin and DER736 plasticizer in a plastic centrifuge tube in turn and mixing them evenly, and then adding 15g of NSA curing agent and 200ul of DMAE catalyst in turn after at least 10 minutes, and each component needs to be fully mixed after adding, and the time interval between adding NSA curing agent and DMAE catalyst is at least 10 minutes.

[0017] Step 2: prepare the resin and acetone to obtain a resin mixture, take at least two portions of the resin mixture, add different amounts of the micro-nano particles to each portion of the resin mixture, mix them evenly and fully to obtain a sample mixture, embed and solidify the sample mixtures of various concentrations on correspondingly set copper meshes and put them into an oven for polymerization, wherein the mesh aperture on the copper mesh is larger than the particle size of the micro-nano particles.

[0018] When preparing the sample mixture, 20ul of the resin and 180ul of the acetone are added to a 1.5ml conical centrifuge tube in sequence to obtain the resin mixture; the micro-nano particles are taken with a toothpick and added to the resin mixture to form the sample mixture. In the above method, the resin mixture is prepared in equal amounts in a single tube in batches, but it can also be prepared uniformly and then taken in equal amounts.

[0019] In this embodiment, 10 different concentrations of the sample mixture are selected and configured. Specifically, 10 tubes of the resin mixture are prepared in equal amounts, and the micro-nano particles are taken 10 times with a toothpick, so that the amount of the micro-nano particles taken each time is increased, and 10 tubes of the sample mixture are mixed to form; the sample mixture is shaken tube by tube using a vortex shaker for 1 minute to achieve full dispersion of the micro-nano particles in the resin and the acetone. The specific concentration ratio of the micro-nano particles and the resin mainly depends on the size of the micro-nano particles. Generally speaking, the smaller the micro-nano particles, the smaller the concentration of the prepared sample mixture; the larger the micro-nano particles, the larger the concentration of the prepared sample mixture. By preparing the sample mixture of various concentrations, it is convenient to obtain an ideal sample after embedding and curing.

[0020] The resin mixture obtained by this embodiment is particularly suitable for the micro-nano particles with a particle size range of 1 to 500um, but the holes of the copper mesh need to be larger than the particle size of the micro-nano particles. Based on the holes set on the copper mesh, the copper mesh is used as a carrier for sample embedding and curing, so that it has a certain transparency under an optical microscope, which is convenient for preliminary screening of samples of appropriate concentrations; secondly, there is a carbon support film at the bottom of the copper mesh, which supports the sample mixture when carrying it, and the carbon support film is transparent to the electron beam. For some particles less than 200nm, in the area where the resin thickness is also less than 200nm, the entire particle morphology can be directly observed and analyzed by the STEM mode of a transmission electron microscope or a scanning electron microscope. The holes on the copper mesh in this embodiment are 300 meshes, and the specific structure of the copper mesh is well known to ordinary technicians in this technical field, and will not be described in detail here.

[0021] After each oscillation is completed to obtain a tube of the sample mixture, 1 ul should be quickly drawn from the tube and dropped on the carbon support film of the copper mesh, and the copper mesh should be placed on tin foil; after obtaining 10 copper meshes with different concentrations of the sample mixture, the 10 copper meshes are placed together in a 60° oven for polymerization for at least 48 hours to complete the embedding and curing of the micro-nanoparticles.

[0022] Step 3: Place the polymerized copper mesh into a FIB-SEM double-beam electron microscope, one at a time, and apply 30 kV of electron voltage. By observing the distribution of the micro-nano particles on the copper mesh, screen out the copper mesh with an average distance between the micro-nano particles between 20 and 500 um to facilitate subsequent operations.

[0023] Step 4: Fix the screened copper mesh to the sample stage tilted in the FIB-SEM dual-beam electron microscope. The inclination of the sample stage varies from manufacturer to manufacturer. In this embodiment, the FIB-SEM dual-beam electron microscope with a 42° tilted sample stage is used.

[0024] Step 5. After the sample stage of the FIB-SEM dual-beam electron microscope is tilted and adjusted, such as by 10°, the micro-nano particles dispersed, centered in the mesh of the copper mesh, and connected with resin around are selected as particle samples, a Pt protective coating is evaporated on the surface to be processed of the particle sample, and the voltage and current are adjusted after cutting it to the target thickness. The angle of the sample stage is fine-tuned within the range of ±3° to thin and refine the particle sample to obtain a thin film sample. During the cutting, thinning and refining process, both ends of the particle sample are ensured to be connected to the resin so that the obtained thin film sample can remain flat.

[0025] Specifically, when evaporating the Pt protective coating, the electrical parameters used are a voltage of 30 kV and a current of 80 pA to 230 pA; when cutting the target area, the electrical parameters used are a voltage of 30 kV and a current of 2.5 to 21 nA; after cutting to a thickness of 1000 nm, a voltage of 30 kV and a current of 790 pA to 80 pA are selected to gradually thin the thickness from 1000 nm to 150 nm, and then a voltage of 5 kV and a current of 230 pA are used for fine-tuning until the thin film sample is obtained.

[0026] Different materials of micro-nano particles are used, and different requirements are imposed on the thinness of the film sample to be formed. When the micro-nano particles are samples that are difficult to be penetrated by electron beams, such as ceramics and metals with relatively large atomic numbers, the thickness of the film sample formed by thinning must be below 80nm; when the micro-nano particles are materials with relatively small atomic numbers, the thickness of the film sample formed by thinning is required to be around 100nm. When forming the film sample, the sample stage of the FIB-SEM dual-beam electron microscope can be rotated to observe the sample cross section and directly measure it, so as to know whether the obtained film sample meets the requirements; the film sample can also be observed by a 5kV electron beam. If the film sample is transparent, it means that the sample has been thinned to a suitable thickness for use.

[0027] Step 6: Transfer the copper mesh with the thin film sample to a TEM for observation and analysis. Figure 5 As shown, in this embodiment, the micro-nano particles of NCM (nickel-cobalt-manganese ternary material) are used to form the imaging image of the thin film sample in TEM, and the thickness thereof can be reduced to about 100 nm using the aforementioned steps. Figure 6 As shown, in the local detail enlargement of the TEM and the selected electron diffraction pattern, the atomic arrangement and single crystal structure diffraction image of NCM (nickel-cobalt-manganese ternary material) can be clearly seen. The resin mixture formed in this embodiment has universality and can be widely used in the field of transmission electron microscope sample preparation in conjunction with the sample preparation method.

[0028] This embodiment changes the traditional FIB-SEM double beam electron microscope, which needs to protect the selected part, cut and extract, and thin the many precision processing steps before obtaining a method suitable for TEM observation samples, effectively reducing the preparation steps and shortening the preparation time. In the process of forming TEM samples, the resin with improved formula is embedded and fixed to fix the micro-nano particles, and the resin will not be thermally deformed and cracked under the electron beam and ion beam, so that the film sample can maintain the connection state with the resin during the process of cutting, thinning and finishing. With the continuous reduction of the sample thickness, the sample is prevented from bending or curling due to the residual stress concentration in the sample, ensuring that a straight and ideal TEM sample is obtained, and effectively improving the success rate of sample preparation. The micro-nano particles in multiple meshes of the same copper mesh can also be processed, and multiple TEM samples can be made at one time, thereby effectively improving the efficiency of sample production.

[0029] The description of the present invention is given for the purpose of illustration and description, and is not intended to be exhaustive or to limit the invention to the disclosed form. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for particular uses.

Claims

1. A method for preparing micro-nanoparticle TEM samples, characterized in that: The following steps are involved: Step 1, preparing a resin for embedding and curing micro-nano particles; Step 2: preparing the resin and acetone to obtain a resin mixture, taking at least two portions of the resin mixture, adding different amounts of the micro-nano particles to each portion of the resin mixture, and mixing them evenly and fully to obtain a sample mixture, embedding and curing the sample mixtures of various concentrations on correspondingly set copper meshes and placing them in an oven for polymerization, wherein the mesh aperture of the copper mesh is larger than the particle size of the micro-nano particles; Step 3, placing the polymerized copper mesh into a FIB-SEM double-beam electron microscope, placing one at a time and applying an electron voltage of 30 kV, and screening out the copper mesh with an average distance between the micro-nano particles between 20 and 500 um by observing the distribution of the micro-nano particles on the copper mesh; Step 4, fixing the screened copper mesh onto a sample stage tilted in the FIB-SEM dual-beam electron microscope; Step 5: After the sample stage of the FIB-SEM dual-beam electron microscope is tilted and adjusted, the micro-nano particles dispersed, centered in the mesh of the copper mesh, and connected with resin around are selected as particle samples, a Pt protective coating is evaporated on the surface to be processed of the particle sample, and the voltage and current are adjusted after cutting it to the target thickness, and the angle of the sample stage is fine-tuned within the range of ±3° to thin and refine the particle sample to obtain a thin film sample. During the cutting, thinning and refining process, both ends of the particle sample are ensured to be connected to the resin so that the obtained thin film sample can remain flat; Step six: transfer the copper mesh with the thin film sample to TEM for observation and analysis.

2. A method for preparing micro-nanoparticle TEM samples according to claim 1, characterized in that: The resin includes the following components: 7 g of ERL4221 epoxy resin, 5 g of DER736 plasticizer, 15 g of NSA curing agent, and 200 ul of DMAE catalyst.

3. A method for preparing micro-nano particle TEM samples as claimed in claim 2, characterized in that: The resin preparation method is as follows: use a plastic pipette to suck and weigh 7g of ERL4221 epoxy resin and 5g of DER736 plasticizer respectively, place the weighed ERL4221 epoxy resin and DER736 plasticizer in a plastic centrifuge tube in turn and mix them evenly, then add 15g of NSA curing agent and 200ul of DMAE catalyst in turn after at least 10 minutes, and fully mix each time a component is added, and the time interval between adding the NSA curing agent and the DMAE catalyst is at least 10 minutes.

4. A method for preparing micro-nano particle TEM samples as claimed in claim 3, characterized in that: When preparing the sample mixture in step 2: take 20ul of the resin and 180ul of the acetone and add them into a 1.5ml conical bottom centrifuge tube in sequence to obtain the resin mixture; The micro-nano particles are taken with a toothpick and added into the resin mixed solution to form the sample mixed solution.

5. A method for preparing micro-nano particle TEM samples as claimed in claim 4, characterized in that: Prepare 10 tubes of the resin mixture in equal amounts, take the micro-nano particles 10 times with a toothpick, increase the amount of the micro-nano particles taken each time, and mix to form 10 tubes of the sample mixture; The sample mixture was shaken tube by tube using a vortex shaker for 1 minute to achieve full dispersion of the micro-nano particles in the resin and the acetone.

6. A method for preparing micro-nano particle TEM samples as claimed in claim 5, characterized in that: After each shaking, a tube of the sample mixture is obtained, and then 1 ul is drawn from the tube and dropped onto the carbon support film of the copper mesh, and the copper mesh is placed on tin foil; After obtaining 10 copper meshes with the sample mixture, put them together in an oven at 60° for polymerization for at least 48 hours.

7. A method for preparing micro-nano particle TEM samples according to claim 1, characterized in that: In step five, the sample stage of the FIB-SEM dual-beam electron microscope needs to be tilted and adjusted by 10°.